Development and initial argument-based validation of a scoring used in the assessment of L2 writing electronic portfolios - Lallmamode, Sheila Parveen (Elsevier, 2016)
Although writing electronic portfolios (ePortfolios) help learners communicate digitally and provide a platform for works to be better collected and presented, challenges are present in their assessment. This paper reports the development and validation of a writing ePortfolio scoring rubric for an action research course for L2 learners. Using Bachman's (2005) 'Assessment Use Argument' as a basis, two main claims to support the validity of the rubric were examined: (1) the rubric is a reliable tool; and, (2) the rubric is relevant to the construct being measured. A mixed-method approach was used in the development and validation of the eight-criteria analytic and holistic evaluation scoring rubric. Thirteen raters evaluated thirty-eight ePortfolios in the study. The analyses of raters' rating using many-facet Rasch measurement approach and raters' individual standardised open-ended interviews indicated that overall the rubric's analytic categories functioned appropriately to assess the intended construct. However, the criterion 'Ease of Navigation' was found to be misfitting due to a differences in raters' evaluation of the same ePortfolios. Overall, the argument-based validation indicated that the scoring rubric is a reliable and valid instrument for the purpose of assessing L2 writing ePortfolios in the context for which it was developed.